Brain-computer interface applications to decrease phantom limb pain - Paula Ivone Rodríguez-Azar (Open Journal of Pain Medicine - Peertechz Publications, 2023)
Phantom limb pain is mainly experienced in people who have suffered limb amputation, its study and analysis are relevant to know the causes and help patients to reduce pain. On the other hand, brain-computer interfaces encode brain signals and decode them for communication with a device. Through the motor imagination of the movement of the amputated limb and with the help of a brain-computer interface, an amputee patient can reduce or eliminate pain. The objective of this paper is to give an introduction to brain-computer interfaces as a tool for the reduction of phantom limb pain. Therefore, the applications of interfaces in relation to pain are highlighted, some related studies are discussed, and their benefits and disadvantages are analyzed. Finally, it is established that phantom limb pain research benefits from incorporating brain-computer interfaces as part of non-pharmaceutical therapy because it is a tool that provides feedback on the reconfiguration of the cerebral cortex in relation to pain.